Effect of soil moisture regimes on the growth and fecundity of slender amaranth (Amaranthus viridis) and redroot pigweed (Amaranthus retroflexus). Issue 1 (3rd January 2021) - Khan, Asad M.; Mobli, Ahmadreza; Werth, Jeff A; Chauhan, Bhagirath S.
Abstract: Slender amaranth ( Amaranthus viridis L.) and redroot pigweed ( Amaranthus retroflexus L.) are increasingly problematic weeds of summer crops in Australia. Water is considered the most limiting factor in an agroecosystem, and water stress adversely impacts the growth and reproduction of plant species. The primary objective of this study was to determine the growth and fecundity of two Australian biotypes (Goondiwindi and Gatton) of A. viridis and A. retroflexus under water-stress conditions. Four water-stress treatments (100%, 75%, 50%, and 25% field capacity [FC]) at a 4-d irrigation interval were chosen. No difference was observed for growth and seed production between the two biotypes of both species when grown under varying soil moisture regimes. At 100% FC, A. viridis produced 44 g plant −1 aboveground biomass and 1, 740 seeds plant −1 . The maximum growth (46 g plant −1 ) and seed production (3, 070 seeds plant −1 ) of A. retroflexus were observed at 100% FC. The growth and seed production of both species were reduced with increased water-stress levels. Both weeds responded to water stress by decreasing the shoot:root biomass ratio. However, A. viridis (290 seeds plant −1 ) and A. retroflexus (370 seeds plant −1 ) were able to produce a significant number of seeds per plant even at 25% FC. Results suggest that both weeds will produce seeds under water-limiting conditions. Therefore, management strategies are required to minimize the growth and survival of weeds in water-deficit conditions.